2017
DOI: 10.1038/s41430-017-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synbiotic supplementation in children and adolescents with cystic fibrosis: a randomized controlled clinical trial

Abstract: Synbiotic supplementation shown promise at diminishing the pro-inflammatory markers IL-6, IL-8 in the SCFG with positive bacteriology and NOx in the SCFG in children/adolescents with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
11
1
1
Order By: Relevance
“…The 9 studies included in this systematic review (Bruzzese et al, 2004 (16), Bruzzese et al, 2007 (17), Weiss et al, 2010 (18), Fallahi et al, 2013 (19), Del Campo et al, 2014 (20), Di Nardo et al, 2014 (21), Jafari et al, 2013 (22), Bruzzese et al, 2014 (23), Bruzzese et al, 2017(12), and de Freitas et al, 2017 (11)) are described in Table 1 part A. The study excluded from the analysis is also described in Table 1 part B: Infant Pina et al, 2008 (15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 9 studies included in this systematic review (Bruzzese et al, 2004 (16), Bruzzese et al, 2007 (17), Weiss et al, 2010 (18), Fallahi et al, 2013 (19), Del Campo et al, 2014 (20), Di Nardo et al, 2014 (21), Jafari et al, 2013 (22), Bruzzese et al, 2014 (23), Bruzzese et al, 2017(12), and de Freitas et al, 2017 (11)) are described in Table 1 part A. The study excluded from the analysis is also described in Table 1 part B: Infant Pina et al, 2008 (15).…”
Section: Resultsmentioning
confidence: 99%
“…Bruzzese et al (12) showed no significant clinical effects of a probiotic preparation in a prospective, randomized, placebo‐controlled study, with one of the largest samples of included patients (12). De Freitas et al (11) focused on inflammatory effects of a synbiotic preparation in children and adolescents with CF and found only mild effects in some of the inflammatory markers (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ministério da Saúde, 2017 A busca de artigos científicos foi realizada nas bases de dados PubMed e BVS por meio dos descritores "fibrose cística" ("cystic fibrosis") e "criança" ("child") combinados com "terapia nutricional" ("nutrition therapy"), "qualidade de vida" ("quality of life") ou "estado nutricional" ("nutritional status"), todos no idioma inglês e com seus respectivos sinônimos. (FREITAS et al, 2018).…”
Section: Introductionunclassified